AI-ML based NLP Development using SVM & RF concepts - Prasad N, Achyutha (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
In this paper, a short survey of the comment based Natural Language Processing System utilizing semi-managed bootstrapping, ML approaches of Support Vector Machine (SVM) and Random Forest (RF) strategy is being introduced basically. How to cite this article: Jipeng T, Neelagar MB, Prasad AN et al. AI-ML based NLP Development using SVM and RF Concepts. J Adv Res Appl Arti Intel Neural Netw 2020; 4(2): 1-2.